Green Development environment and sustainability in a developing world - Adams, W.M. (London Routledge, 2009)
The concept of sustainability lies at the core of the challege of enviroment and development, and the way Governments, business and enviromental groups respond to it. Green Development provides a clear and coherent analysis of sustainable development in both theory and practice.
Includes bibliographical references (p. (380-440)
Keywords: Sustainable Development